2017
DOI: 10.1159/000455850
|View full text |Cite
|
Sign up to set email alerts
|

New Genetic Diagnoses of Short Stature Provide Insights into Local Regulation of Childhood Growth

Abstract: Idiopathic short stature is a common condition with a heterogeneous etiology. Advances in genetic methods, including genome sequencing techniques and bioinformatics approaches, have emerged as important tools to identify the genetic defects in families with monogenic short stature. These findings have contributed to the understanding of growth regulation and indicate that growth plate chondrogenesis, and therefore linear growth, is governed by a large number of genes important for different signaling pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 159 publications
0
29
0
1
Order By: Relevance
“…Normal growth in children requires not only a normal GH–IGF-I axis but also normal local signals and environments within the epiphyseal growth plate. Recent studies have shown that many factors independent of the GH – IGF-I system regulate this growth plate, including paracrine signals, extracellular matrix, and intracellular mechanisms of chondrocytes [ 13 - 15 ]. Phenotypic spectrums of these related genes exist.…”
Section: Genetic Causes Of Issmentioning
confidence: 99%
“…Normal growth in children requires not only a normal GH–IGF-I axis but also normal local signals and environments within the epiphyseal growth plate. Recent studies have shown that many factors independent of the GH – IGF-I system regulate this growth plate, including paracrine signals, extracellular matrix, and intracellular mechanisms of chondrocytes [ 13 - 15 ]. Phenotypic spectrums of these related genes exist.…”
Section: Genetic Causes Of Issmentioning
confidence: 99%
“…Among these, WWTR1/TAZ, HDAC4, TWIST2, and PRKD1 are known to interact with RUNX2, an essential osteoblastic differentiation factor. Several genes harbor Mendelian mutations resulting in abnormal bone density or skeletal phenotypes [22][23][24][25][26]34,35,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] , and many also show abnormal mouse skeletal phenotypes ( Table 2). Although further work is needed to concretely link many of these GWAS-implicated variants to their corresponding target effector genes, our promoter Capture-C approach did corroborate some of these genes as putative functional effector genes acting in bone accrual.…”
Section: Discussionmentioning
confidence: 99%
“…In den langen Röhrenknochen bilden sich jeweils am Ende des zukünftigen Knochens Ossifikationszentren, zwischen denen knorpelige Wachstumsfugen, die Epiphysenfugen, entstehen. Die grundlegenden zellulären Prozesse werden durch hormonelle, parakrine und autokrine Signale begleitet [2] und durch Eigenschaften von Bindegewebsproteinen und mechanische Stimulation der Wachstumsfuge reguliert [3]. Wachstumsfugen sind nicht nur für das Wachstum der langen Röhrenknochen, sondern auch für das Wachstum der Wirbelsäule und des Gesichtsskeletts verantwortlich.…”
Section: Einführungunclassified